2021
DOI: 10.1007/s11240-021-02078-3
|View full text |Cite
|
Sign up to set email alerts
|

Actisil application affects growth, flowering, and biochemical parameters in petunia in vitro and greenhouse

Abstract: Mineral nutrients are necessary for the growth and development of plants. Previous studies have concentrated mainly on silicon-accumulating plants, while less work has been conducted on non-accumulating plants such as Petunia × atkinsiana D. Don. In this study, we investigated the responses of morphological (plant height, root length, fresh and dry weight, no. of flowers) and biochemical (proline, malondialdehyde MDA, catalase CAT activity, total chlorophylls, carotenoids, total polyphenol, and NO3) traits of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Because the essentiality of Si in higher plants has not been demonstrated yet (Marschner, 2012), the stimulation of plant growth after its application could not be expected. Despite that, some authors have observed that Si promotes vegetative growth in different crops (Kornd€ orfer and Lepsch, 2001;Krupa-Małkiewicz and Calomme, 2021;Liang et al, 2015;Pati et al, 2016;S a et al, 2015), particularly when plants are under biotic and abiotic stress conditions (Ma, 2004). Furthermore, the highest Si concentration in plants was observed in the roots.…”
Section: Discussionmentioning
confidence: 99%
“…Because the essentiality of Si in higher plants has not been demonstrated yet (Marschner, 2012), the stimulation of plant growth after its application could not be expected. Despite that, some authors have observed that Si promotes vegetative growth in different crops (Kornd€ orfer and Lepsch, 2001;Krupa-Małkiewicz and Calomme, 2021;Liang et al, 2015;Pati et al, 2016;S a et al, 2015), particularly when plants are under biotic and abiotic stress conditions (Ma, 2004). Furthermore, the highest Si concentration in plants was observed in the roots.…”
Section: Discussionmentioning
confidence: 99%
“…blueberry [Morikawa andSaigusa 2004, Figiel-Kroczyńska andOchmian 2019], and non-accumulating plants e.g. petunia [Krupa-Małkiewicz and Calomme 2021]. Numerous authors described a positive role of Si in improving crop growth and yield under abiotic and biotic stress conditions by increasing the activity of antioxidant enzymes like CAT, increased accumulation of proline and malondialdehyde concentration (MDA), the secretion of endogenous hormones, and the production of lignins, chitinase, phenolic compounds, phytoalexin, and glucanases [Sahebi et al 2016, Luyckx et al 2017, Mandlik et al 2020.…”
Section: Introductionmentioning
confidence: 99%